2000
DOI: 10.1034/j.1600-9657.2000.016003116.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different techniques for obturating experimental internal resorptive cavities

Abstract: Forty extracted maxillary central incisors were instrumented at the working length to a #50 file. The roots were sectioned transversely with a diamond disk at 7 mm from the anatomical apex. At the opening of the root canal of each section, hemicircular cavities were drilled with a specially designed bur. The corresponding root sections were cemented with glue, thus obtaining root canals with similar cavities that simulated internal resorptions. Teeth were embedded in plaster casts to facilitate their handling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 13 publications
(16 reference statements)
1
33
0
3
Order By: Relevance
“…However, several authors have suggested endodontic treatment, to arrest the destructive process, for cases without external perforation as soon as internal resorption is detected (12,13).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, several authors have suggested endodontic treatment, to arrest the destructive process, for cases without external perforation as soon as internal resorption is detected (12,13).…”
mentioning
confidence: 99%
“…The persistence of organic debris and bacteria in these irregularities may interfere with the long-term success of the endodontic treatment (12). Therefore, the importance of achieving total obliteration of the root canal space has been stressed in case of internal resorption (14).…”
mentioning
confidence: 99%
“…Treatment generally consists of the preparation of the canal to the apical foramen with particular emphasis on irrigation and ultrasonication so that the resorbed area is cleansed as thoroughly as feasible. The obturation of the canal can be achieved by a variety of techniques including hot vertically condensed gutta-percha, Obtura-delivered hot gutta-percha 18 and more recent innovations such as the Microseal technique.…”
Section: (2) Intraradicularmentioning
confidence: 99%
“…Os resultados obtidos mostraram haver diferença significativa entre as duas incidências radiográficas apenas nos dentes obturados com o sistema ultrassônico, o que está de acordo com os estudos de Goldberg et al 9 e Agarwal et al 7 , que observaram também um menor grau de preenchimento da cavidade de reabsorção na incidência mesiodistal em relação à vestibulolingual.…”
Section: Segundo Parkunclassified
“…Inúmeros equipamentos e técnicas têm sido testados na obturação das cavidades de reabsorção interna 7,9 , sejam estas, condensação lateral e vertical apenas, e uso de um compactador termomecânico e de um sistema termoplastificador, como o Thermafil®. No entanto, nenhuma destas técnicas mostrase satisfatória quanto ao preenchimento total das áreas de reabsorção.…”
Section: Introductionunclassified